Pengembangan Karier sebagai Faktor Penentu Kinerja Karyawan PT. Telkom Makassar - Muliati; Yasin, Nurfatwa Andriani (Jurnal Online Manajemen ELPEI, 2025)
This study aims to examine the influence of career development on employee performance at PT. Telkom Makassar. The population elements in this study were 136 employees at PT. Telkom, which were then all of these populations were sampled. This study consists of career development and performance variables. Career development with indicators of promotion opportunities, training and development, and fairness in career opportunities. The analysis method used in this study is correlation analysis. This study found the equation Y = 0.002 + 0.652X1 + 0.112X2 +0.235X3. The correlation between promotion opportunities and employee performance is very strong with a value of 0.931, followed by the correlation between fairness in career opportunities and employee performance with a correlation value of 0.841, and finally the correlation between training and development and employee performance of 0.822.